2022
DOI: 10.1016/j.hemonc.2020.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Autoimmune Storm After a Single Cycle of Anti-PD-1 Therapy

Abstract: As immunotherapy agents are incorporated into the routine oncological practice, the number of patients at the risk of immune-related adverse events has increased dramatically. However, the prompt identification and effective management of severe autoimmune complications remain a challenge. We report the case of a patient with metastatic lung adenocarcinoma who experienced a fatal autoimmune storm 3 weeks after the first dose of anti-programmed death receptor-1 (PD-1) agent pembrolizumab, which included thyroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 18 publications
0
17
0
1
Order By: Relevance
“…There was no consistent pattern of preexisting autoimmune conditions—only one patient had a prior autoimmune disease [5]. Twenty‐two patients were reported to have concomitant myasthenia gravis [4, 6–18]. The median number of doses to the development of IM3OS was one.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There was no consistent pattern of preexisting autoimmune conditions—only one patient had a prior autoimmune disease [5]. Twenty‐two patients were reported to have concomitant myasthenia gravis [4, 6–18]. The median number of doses to the development of IM3OS was one.…”
Section: Resultsmentioning
confidence: 99%
“…Todo et al described a case of seronegative myasthenia gravis, although electrodiagnostic testing was reported to be negative [27]. Anti‐AChR antibodies were reported to be positive in the majority of cases in which concurrent myasthenia gravis was diagnosed [4, 6, 7, 10–12, 21, 28].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Myositis may either occur concurrently with, or precede the development of, MG. Conversely, myocarditis always seems to follow MG (Shah et al., 2015). Importantly, a previous study found that myositis and/or myocarditis occur concomitantly with MG, and are frequently related to poor outcomes (Fuentes‐Antrás et al., 2020). There were 35 cases of MG complicated with myocarditis in our review, and the death group accounted for 57.14% (20/35).…”
Section: Discussionmentioning
confidence: 99%